Social Deception Through Narrative Rationality Celebrity Drug Users - Muh. Adhaarfa SIALA; Andi Mirza RONDA; Dewi WIDOWATI (International Journal of Environmental, Sustainability, and Social Science, 2023)
When arrested by the authorities, celebrities always insist that they use drugs to work, just as users, just trying, because of the work environment, deliberately targeted by the police or BNN, police engineering, they are framed. Jefri Nichol was one of the celebrities who made such a statement. The purpose of the study was to assess the rationality of Jefri Nichol's drug-related narrative. The study used Walter R. Fisher's Narrative Paradigm and Barbara O'Keefe's Theory of Message-Making Logic. Methodologically, research is an interpretive paradigm with case study methods. The subject of his research was Jefri Nichol and his statements in the media as his object. The results of the study showed that Jefri Nichol's was inconsistent. Before the case, Jefri Nichol knew the negative impact of drugs on his life and career. After being caught in the narrative, drug use is just trial and error because of work. During the examination of the police, the court, and undergoing rehabilitation, Jefri Nichol produced a narrative of victimhood in which the final motive was the reduction of punishment, image, existence, and economy. Keywords: Narrative Paradigm, Celebrity, drug users